2008
DOI: 10.1093/rheumatology/ken371
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of serum amyloid A 1.1 to degradation by MMP-1: potential explanation for higher risk of type AA amyloidosis

Abstract: These results may explain the higher risk of amyloidosis in patients with a SAA1.1/1.1 genotype vs SAA1.5/1.5 or SAA1.1/1.5 genotype. In addition, the impaired degradation of SAA1.5 by MMP-1 could also explain the higher serum SAA concentrations in persons with a SAA1.5 genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
0
27
0
2
Order By: Relevance
“…Further confirmation was recently provided by the Nijmegen group of investigators (38), who demonstrated that susceptibility to MMP-1 degradation is highly dependent on SAA1 genotype. Significantly, SAA1.1 but not SAA1.5 is largely cleaved by MMP-1 between residues 57 and 58, and this proteolytic event is related to the presence of Ala 57 , which belongs to both SAA1.1 and SAA1.3 isoforms but is absent in SAA1.5 (38). Therefore, these data seem to be in agreement with the accelerated clearance of SAA1.1 and SAA1.3 compared with SAA1.5 and point to the possibility that susceptibility to N-terminal cleavage at residue 57 might be related to the higher risk of development of AA associated with these genotypes.…”
Section: Prevalence Of Aa Amyloidosis In Rheumatic Diseasesmentioning
confidence: 74%
See 1 more Smart Citation
“…Further confirmation was recently provided by the Nijmegen group of investigators (38), who demonstrated that susceptibility to MMP-1 degradation is highly dependent on SAA1 genotype. Significantly, SAA1.1 but not SAA1.5 is largely cleaved by MMP-1 between residues 57 and 58, and this proteolytic event is related to the presence of Ala 57 , which belongs to both SAA1.1 and SAA1.3 isoforms but is absent in SAA1.5 (38). Therefore, these data seem to be in agreement with the accelerated clearance of SAA1.1 and SAA1.3 compared with SAA1.5 and point to the possibility that susceptibility to N-terminal cleavage at residue 57 might be related to the higher risk of development of AA associated with these genotypes.…”
Section: Prevalence Of Aa Amyloidosis In Rheumatic Diseasesmentioning
confidence: 74%
“…Subsequently, in vitro studies confirmed that human SAAs and AA amyloid fibrils are susceptible to proteolytic cleavage by MMPs, generating fragments of different sizes (37). Further confirmation was recently provided by the Nijmegen group of investigators (38), who demonstrated that susceptibility to MMP-1 degradation is highly dependent on SAA1 genotype. Significantly, SAA1.1 but not SAA1.5 is largely cleaved by MMP-1 between residues 57 and 58, and this proteolytic event is related to the presence of Ala 57 , which belongs to both SAA1.1 and SAA1.3 isoforms but is absent in SAA1.5 (38).…”
Section: Prevalence Of Aa Amyloidosis In Rheumatic Diseasesmentioning
confidence: 86%
“…In humans, SAA-1 is also the precursor of reactive amyloid fibrils in type AA amyloidosis, a condition caused by deposition of insoluble fibrillar amyloid proteins (a degraded N-terminus fragment of SAA) in the extracellular space in many organs and tissues (Merlini and Bellotti 2003). Several alleles have been discovered with different susceptibilities to amyloid formation, e.g., SAA1.1 is more susceptible than SAA1.5 (van der Hilst et al 2008). …”
Section: Saa-1mentioning
confidence: 99%
“…The SAA1.1 (α) isoform is more susceptible to cleavage by MMP-1 than SAA1.5 (β), resulting in a higher production of the 1-57 fragments from SAA1 . 1 (α) [29] .…”
Section: Discussionmentioning
confidence: 99%